The mediatory role of inflammatory markers on the relationship between the NOVA classification system and obesity phenotypes among obese and overweight adult women: a cross-sectional study - Hajmir, Mahya Mehri; Shiraseb, Farideh; Hosseininasab, Dorsa; Aali, Yasaman; Hosseini, Shabnam; Mirzaei, Khadijeh (Frontiers in Nutrition, 2023)
Background: Diet and inflammation both play important roles in the occurrence of obesity. We aim to investigate the role of inflammation on the development of both metabolically healthy obese (MHO) and metabolically unhealthy obese (MUHO) individuals. Methods: This cross-sectional study included 221 females, aged 18 to 56 yeas, who were overweight and obese. The study assessed the metabolic health phenotypes of the participants using the Karelis score. Additionally, dietary intakes were evaluated using a 147-item semi-quantitative questionnaire and the NOVA classification system (comprising 37 food groups and beverages). The study also collected and analyzed the blood parameters, as well as biochemical and anthropometric indices, for all participants. Results: Among the women included in the study, 22.9% had MHO phenotypes, while 77.1% had MUHO phenotypes. A significant association between the third quartile of the NOVA classification system and increased likelihood of having the MUHO phenotype was observed (OR = 1.40, 95% CI= 1.09-4.92, P=0.04). Regarding the potential role of inflammatory markers, high-sensitivity C-reactive protein (hs-CRP) (P=0.84), transforming growth factor-β (TGF-β) (P=0.50), monocyte chemoattractant protein-1(MCP-1) (P=0.49), plasminogen activator inhibitor-1(PAI-1) (P=0.97), and homeostatic model assessment for insulin resistance (HOMA-IR) (P=0.92), were found to be mediators. Conclusion: We observed a significant positive association between ultra-processed food (UPF) consumption and MUHO phenotype in overweight and obese women. This association appeared to be mediated by some inflammatory markers such as hs-CRP, TGF-β, MCP-1, PAI-1, and HOMA-IR. Additional studies are needed to validate these findings.